Conducting the Needs Assessment #5: Phase 1—Pre-assessment - Savanna Turner; Matthew Benge (EDIS)
This new 5-page publication is the fifth in the Conducting the Needs Assessment series. The preassessment phase, also known as the exploration phase, of conducting a needs assessment includes defining the purpose, identifying existing information, and determining the appropriate methods to conducting the needs assessment. Extension professionals and service providers should complete the preassessment phase prior to conducting the actual needs assessment. Written by Savanna Turner and Matt Benge.